2014
DOI: 10.1213/ane.0000000000000066
|View full text |Cite
|
Sign up to set email alerts
|

Transversus Abdominis Plane Block to Ameliorate Postoperative Pain Outcomes After Laparoscopic Surgery

Abstract: TAP block is an effective strategy to improve early and late pain at rest and to reduce opioid consumption after laparoscopic surgical procedures. In contrast, the TAP block was not superior compared with control to reduce early and late pain during movement. Preoperative administration of a TAP block seems to result in greater effects on postoperative pain outcomes. We also detected a local anesthetic dose response on late pain and postoperative opioid consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
125
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(128 citation statements)
references
References 60 publications
(73 reference statements)
3
125
0
Order By: Relevance
“…TAP blocks have been reported to reduce postoperative VAS, morphine consumption, and systemic analgesic requirements, and to reduce opioid-related side effects after abdominal surgeries, including laparoscopic surgery, as compared with placebo blocks [2,[14][15][16][17][18]. Previous reports have shown TAP blocks provide significant pain relief from within 2 hours of laparoscopic surgery, but not at 24 hours postoperatively [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…TAP blocks have been reported to reduce postoperative VAS, morphine consumption, and systemic analgesic requirements, and to reduce opioid-related side effects after abdominal surgeries, including laparoscopic surgery, as compared with placebo blocks [2,[14][15][16][17][18]. Previous reports have shown TAP blocks provide significant pain relief from within 2 hours of laparoscopic surgery, but not at 24 hours postoperatively [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have suggested that minimizing the dose of opioid analgesics could reduce the side effects (30). The previous meta-analyses in adult have demonstrated the significant reduction of opioid usage in regional anesthesia treated adults group while comparing with placebo treated group, and the side effect of opioids such as nausea, sedation, and pruritus were reduced due to the lower opioid consumption (14,31,32). Thus, for children, we speculated that the treatment of TAP block may reduce the occurrence of side effect related with opioid analgesics through the decrease of opioid usage.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we did not observe the significant difference in the time of first opioid analgesic requirement between TAP block and control group. As the first time of opioid usage are usually at the early stage after surgery (14,21,22,25), we speculated that TAP block cannot fully alleviate the early postoperative pain. However, as the time passed, the analgesia effect of TAP block gradually played a role on the postoperative pain management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations